A note on the nocturnal beetle fauna of Lalang Island in the Straits of Malacca - Abdullah, Fauziah (Malaysian Journal of Science, 2008)
A total of 135 specimens were sampled, comprising of 15 species from 8 families of beetles. The species were Casnoidea sp. (Carabidae), Plandones sp. (Cerambycidae) Noserius sp. (Cerambycidae), Cheorane modesta (Chrysomelidae), Veranio discolor (Coccinellidae), Xanthopenthes sp. (Elateridae), Oxyropterus audoniwi (Elateridae), Anomala pallida (Scarabeidae), Apogonia tribicollis (Scarabeidae), Pachycorinus sp. (Staphylinidae), Amarygmus sp. (Tenebrionidae), Obriomaia sp. (Tenebrionidae) and Alphitobius diaperinus (Tenebrionidae). All species identified are 13 first records for Lalang Island. Two species from family Scarabaeidae coded as Scara 6 and Scara 8 were unidentified.A total of 135 specimens were sampled, comprising of 15 species from 8 families of beetles. The species were Casnoidea sp. (Carabidae), Plandones sp. (Cerambycidae) Noserius sp. (Cerambycidae), Cheorane modesta (Chrysomelidae), Veranio discolor (Coccinellidae), Xanthopenthes sp. (Elateridae), Oxyropterus audoniwi (Elateridae), Anomala pallida (Scarabeidae), Apogonia tribicollis (Scarabeidae), Pachycorinus sp. (Staphylinidae), Amarygmus sp. (Tenebrionidae), Obriomaia sp. (Tenebrionidae) and Alphitobius diaperinus (Tenebrionidae). All species identified are 13 first records for Lalang Island. Two species from family Scarabaeidae coded as Scara 6 and Scara 8 were unidentified.